Is the Helmholtz–Kohlrausch Effect More Robust in Women?. (June 2020) - Foutch, Brian K.; Bassi, Carl J.
For gray or achromatic objects, brightness is a relatively simple transformation where very low luminance levels are perceived as black and higher levels are perceived as white. For chromatic objects, the transformation is more complex, depending on color purity as well. This influence of color purity on a color's perceived brightness is a well-established phenomenon known as the Helmholtz–Kohlrausch (H-K) effect. We investigated gender differences in the H-K effect by measuring brightness (via direct brightness matching [DBM]) and luminance (via heterochromatic flicker photometry [HFP]) at five wavelengths (450, 520, 560, 580, and 650 nm) perceived as blue, green, green-yellow, yellow, and red hues. We compared DBM/HFP ratios between 13 males and 18 females. Based on previous evidence of a female advantage in chromatic processes, we hypothesized that DBM/HFP ratios would be higher in female subjects. While HFP measures were essentially the same between male and female subjects, DBM measures and DBM/HFP ratios were significantly higher for female subjects than males. There were no significant effects of contraceptive use based on a post hoc comparison. We also derived simple models of brightness as a function of luminance and saturation, which further suggest gender dimorphism in the H-K effect.